La responsabilidad penal de las personas jurídicas en delitos informáticos en el cantón Quevedo - León Toala, Kerly Vanessa (2025)
The importance of addressing cybercrimes committed by legal entities in the Quevedo canton lies in their significant impact due to the increasing use of technology for cyber thefts, which are on the rise and affecting society. This work focuses on evaluating the sufficiency of Ecuadorian laws to tackle these crimes, with the aim of identifying areas for improvement. Interviews were conducted with judges in the criminal area of Quevedo canton, using questions that range from the definition of cybercrimes to the effectiveness of Ecuadorian laws. The methods include a qualitative analysis of the responses obtained to identify common patterns and ideas among the interviewees. The results show a lack of resources, training, and speed in the processes, as well as a reluctance to report by the affected parties.